2018
DOI: 10.1186/s42269-018-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Active compounds and biological activity of in vitro cultures of some Echinacea purpurea varieties

Abstract: Background: Plant cell cultures have developed rapidly in recent years for the synthesis of selected natural products. This study was conducted to evaluate the effect of yeast extract, jasmonic acid, phenylalanine, and tyrosine on total caffeic acid and polysaccharide production in callus cultures of two Echinacea varieties, namely Double Decker and Rubinstern. The biological activities (antioxidant, antimicrobial and cytotoxic activities) of different Echinacea extracts were also evaluated. Results: Data reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Al Khateeb et al ( 2017 ) reported enhanced phenolic production along with new phenolic compounds that were not initially present in control plants in micro-shoots of Rumex cyprius from 50 to 200 mg/L YE concentration in the medium. Elicitation with YE has successfully increased caffeic acid in Echinacea puprea callus cultures (Rady et al 2018 ), asiaticoside in Centella asiatica and plumbagin in Drosera burmanii whole plant cultures (Kim et al 2004 ; Putalun et al 2010 ) and mitragynine in shoot cultures of Mitragyna speciose (Wungsintaweekul et al 2012 ). Per our results, YE (50 and 100 mg/L) downregulated the apignenin production, while in the contrary, decreased the caffeic acid and apignenin accumulation in the presence of PE and YE in Phoenix dactylifera cell suspension cultures (Al-Khayri and Naik 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Al Khateeb et al ( 2017 ) reported enhanced phenolic production along with new phenolic compounds that were not initially present in control plants in micro-shoots of Rumex cyprius from 50 to 200 mg/L YE concentration in the medium. Elicitation with YE has successfully increased caffeic acid in Echinacea puprea callus cultures (Rady et al 2018 ), asiaticoside in Centella asiatica and plumbagin in Drosera burmanii whole plant cultures (Kim et al 2004 ; Putalun et al 2010 ) and mitragynine in shoot cultures of Mitragyna speciose (Wungsintaweekul et al 2012 ). Per our results, YE (50 and 100 mg/L) downregulated the apignenin production, while in the contrary, decreased the caffeic acid and apignenin accumulation in the presence of PE and YE in Phoenix dactylifera cell suspension cultures (Al-Khayri and Naik 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Barnes et al, 2005). The study of different extracts of E. purpurea showed antioxidant activity of 89.2% (Rady et al, 2018). Stanisavljević et al (2009) found DPPH scavenging activity for ethanol extracts of E. purpurea 93.6% and antimicrobial activity.…”
Section: Resultsmentioning
confidence: 94%
“…Based on the effect of cultivation method on the caffeic acid derivatives content, which are essential substrates for production and biosynthesis of different immunological drugs, the previous researches showed that the total root content of caftaric acid, chlorogenic acid, and chicoric acid in open-field cultivation method were 4.35, 5.02, and 28.06 mg g −1 DW, respectively 41 . However, in vitro cultivation of E. purpurea in basal medium (MS-medium) with 3% sucrose and 0.7% agar showed the maximum 3.66 mg g −1 DW caffeic acid content 42 . Comparing of the obtained results in this study with previous researches indicates the efficiency of hydroponic cultivation system for increasing of caffeic acid derivatives of E. purpurea .…”
Section: Resultsmentioning
confidence: 99%